Pengaruh Customer Experience Terhadap Revisit Intention di The Premiere Hotel Pekanbaru - Fadilla Oktaviani; Feriantano Sundang Pranata; Iqbal Harifal (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
This study aims to analyze the effect of Customer Experience on Revisit Intention at The Premiere Hotel Pekanbaru. The study employed a quantitative approach with a causal associative research design. The sample consisted of 100 respondents selected using a purposive sampling technique, namely guests who had stayed at The Premiere Hotel Pekanbaru. Data were collected through a questionnaire using a Likert scale. The data were analyzed using descriptive analysis with the Respondents' Achievement Level (TCR), classical assumption tests, and simple linear regression analysis with SPSS version 27. The descriptive analysis showed that the Customer Experience variable achieved a TCR score of 79.23%, while the Revisit Intention variable achieved 79.35%, both of which were categorized as good. The results of the simple linear regression analysis indicated that Customer Experience had a positive and significant effect on Revisit Intention, with a regression coefficient of 0.778 (p < 0.05). Furthermore, the coefficient of determination (R²) of 0.886 indicates that 88.6% of the variance in Revisit Intention can be explained by Customer Experience, while the remaining 11.4% is influenced by other factors outside the research model. These findings indicate that better Customer Experience leads to higher Revisit Intention among guests at The Premiere Hotel Pekanbaru.